Towards a Definition of Terrorist Ideology - Ackerman, Gary A. (Terrorism and political violence, 2021)
While conventional wisdom holds that the ideology espoused by a terrorist organization is somehow related to that organization’s actions, the precise nature of the relationship between these phenomena is hotly debated, with scholarship often yielding contrasting empirical results. We argue that one reason for this divergence in viewpoints and research findings is an inadequate understanding of what ideology actually is and how it relates to terrorism. Indeed, the terrorism literature reveals widely disparate uses of the concept of terrorist ideology. This article endeavors to provide a common framework for approaching ideology in the context of terrorism studies by systematically building a new definition of terrorist ideology from first principles. In so doing, we introduce a definition of terrorist ideology that is logically consistent, has robust theoretical underpinnings, and connects the study of ideology within terrorism to broader disciplinary research traditions regarding ideology. This provides a conceptual foundation from which to examine terrorist ideology in an objective, systematic manner and thereby enables terrorism researchers to more productively investigate important outstanding questions, such as which aspects of an ideology are most relevant to violent behavior.